BLOCKCHAIN TECHNOLOGY APPLICATION IN BANKING SYSTEM-AN EMPIRICAL STUDY - K H, Gurumurthy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Blockchain technology has been gaining significant attention in the banking sector due to its potential to transform the industry by enhancing security, efficiency, and transparency. The Blockchain is a technology that will allow transactions simply, safely, effectively, and also safely. In layman’s terms, Block- chain is a data structure that stores transactional records while also ensuring security, efficiency, transparency and decentralization. In a Blockchain, data is stored which is tamper-proof and cannot be changed as it uses encryption and digital signatures on every transaction on a blockchain, which proves the authenticity of the block- chain. To change a record on a blockchain, one needs to change several records, and one needs to change the distributed ledger. It’s quite impossible to change the data which has already been entered into a Blockchain. This is a very promising technology. It’s already in a lot of places. It can also solve any problem in the banking sector. This technology became famous after introducing the first cryptocurrency, which is known as bitcoin. The Blockchain has evolved to address various challenges in the Banking sector. This paper will demonstrate transacting over a secure, blockchain-based network and therefore eliminate the need for intermediary entities. The purpose of this paper is to provide a review of the application and opportunities of the Blockchain for a secure banking system and then the working method of the Blockchain technology has been introduced with analysis. The use of blockchain technology for secure banking has been discussed. The main achievement of this paper is to demonstrate how the Blockchain works and how it can be useful in the secure banking industry.